Exploration of the Impact of ESG on Corporate Financial Performance - Ren Wenxiang (SHS Web of Conferences, 2025)
Within the framework of sustainable investment, the role of corporate engagement in Environmental, Social, and Governance (ESG) aspects has progressively garnered significant public interest. This study investigates the impact of corporate ESG performance on financial outcomes, utilizing constituent firms of the China CSI 300 Index as research samples. The ESG ratings from SynTao Green Finance serve as the proxy for corporate ESG performance, while Return on Equity (ROE) is employed to measure financial performance. Utilizing multiple linear regression analysis supplemented with robustness tests and sectoral differentiation assessments, the empirical results demonstrate that enhanced ESG performance significantly and positively correlates with corporate financial metrics, with the findings maintaining robust consistency across model specifications. Heterogeneity analysis reveals differentiated effects across industries, particularly noting that ESG initiatives in non-manufacturing enterprises exhibit more pronounced financial impacts compared to their manufacturing counterparts. These empirical insights provide valuable references for corporate strategic planning and institutional investors’ portfolio allocation decisions in sustainable finance practices.